PENGARUH LITERASI KEUANGAN DAN FINANCIAL TECHNOLOGY TERHADAP PENGELOLAAN KEUANGAN PRIBADI MAHASISWA - Wahyu Dwi Sukma; Andi Basru Wawo; Fitriaman (Accounting Student Series on Emerging Trends, 2026)
This study aims to determine and analyze the effect of financial literacy and financial technology on the personal financial management of students of the Accounting Department, Faculty of Economics and Business, Halu Oleo University. The sample of this study used a purposive sampling technique with a total of 92 students in the Accounting Department, Faculty of Economics and Business, Halu Oleo University. Methods of data collection using a questionnaire. Data analysis used descriptive analysis methods and multiple regression analysis with the help of the IBM SPSS Statistics version 26 program. The results of this study indicate that (1) Financial Literacy has a significant effect on Personal Financial Management. (2) Financial technology has a significant effect on Personal Financial Management. (3) Financial Literacy and Financial technology simultaneously have a significant effect on Personal Financial Management.